SELF-RESILIENCE OF LOUISA CLARK AS REFLECTED IN JOJO MOYES’ ME BEFORE YOU: (CHARACTER ANALYSIS) - Adisti Supit (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this study is to reveal the self-resilience of Louisa Clark as reflected in Jojo Moyes’ Me Before You. In this research, the writers employ the qualitative method. Two kinds of sources are used in this research: primary and secondary sources. Moyes’ Me Before You is the primary source and the secondary sources are academic articles, books, and websites related to the topic. To collect the data, the writers employ the library research technique. The data obtained is analyzed by using the psychological approach. It means that the study is focused on the psychological aspects of Louisa Clark based on her condition and background as reflected in Moyes’ Me Before You without considering the external factors. The findings show that Louisa Clark demonstrates self-resilience in her thought and actions. Louisa Clark shows her personality by being indulgent and having high self-esteem. They illustrate her self-resilience in her thought. Clark’s personal qualities reflects her will and action in facing the obstacles.